2021
DOI: 10.1016/j.devcel.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cells represent a dynamic stem cell niche governing proliferation and tissue regeneration

Abstract: Highlights d Deletion of Caspase-9 in hair follicle stem cells delays the apoptotic cascade d Apoptotic hair follicle stem cells release Wnt3 and instruct proliferation d A caspase-3/Dusp8/p38 module is responsible for Wnt3 induction in apoptotic cells d Casp-9 fl/fl mice display accelerated wound repair and de novo hair follicle neogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…The main difference between the two cases is the amount of time deleterious cells spend in the tissue before being removed by immune cells. Interestingly, similar phenomena take place in vertebrate epithelia and exactly the same actors appear to be in place 40 .…”
Section: Discussionmentioning
confidence: 61%
“…The main difference between the two cases is the amount of time deleterious cells spend in the tissue before being removed by immune cells. Interestingly, similar phenomena take place in vertebrate epithelia and exactly the same actors appear to be in place 40 .…”
Section: Discussionmentioning
confidence: 61%
“…Recently the unique role of apoptosis during steady-state regeneration was shown in hair follicle stem cell (HFSC) self-renewal and differentiation. It was shown that deficiency of caspase-9, a crucial apoptotic initiator caspase, leads to accumulation of caspase-3 and inappropriate mitogenic signaling by continuously releasing Wnt3 from apoptotic HFSCs and instructing proliferation ( 70 ). Also, in the intestine a link between stem cell proliferation and apoptosis was shown.…”
Section: Discussionmentioning
confidence: 99%
“…So far, this process was mostly characterised either in conditions of massive death induction through irradiation and genetic induction of apoptosis in large domains [31, 32], or through the perturbation of the core apoptotic pathway (e.g. : by blocking some of the essential caspases, caspase3 in Drosophila [33], or caspase9 in mammalian epidermis[34]). However, to our knowledge there is no study that has clearly identified biases in cell proliferation distribution in the vicinity of physiological apoptosis in vivo .…”
Section: Discussionmentioning
confidence: 99%